Asymmetric Effect of Oil Price Change on Inflation: Evidence from Sub Saharan Africa Countries - Babuga, Umar Tijjani; Naseem, Niaz Ahmad Mohd (International Journal of Energy Economics and Policy, 2020)
This study is aimed at investigating the asymmetric effect of oil price on inflation for Sub Saharan Africa (SSA) countries. Based on the findings from the dynamic heterogenous nonlinear panel ARDL estimation, a panel data representation of Shin et al. (2014), the long run asymmetric relationship exists between both oil price increase (op+) and decrease (op-) and inflation for these countries. Nevertheless, the oil price increase tends to exert more effect on inflation than the oil price decrease. For policy implication, the monetary authorities shall pay more attention to the increase in oil price than the oil price decrease in designing appropriate policies of price stability as the former exerts greater impact on inflation than the latter. The price stability as one of the key macroeconomic goals could be attained if these countries understand the oil price-inflation relationship and then monetary measures can be adjusted to endure the effect of oil price changes especially increase in oil price on the price level so that stability in the prices of output can be maintained. Keywords: Panel data, inflation, Asymmetry, Sub Saharan Africa JEL Classifications: C33, E31, E3 DOI: https://doi.org/10.32479/ijeep.10764